2022
DOI: 10.3390/buildings12040456
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Bond-Slip Behavior of Circular/Squared Concrete-Filled Steel Tubes

Abstract: Numerous existing formulas predicted the ultimate interfacial bond strength in concrete-filled steel tubes (CFST) between steel tubes and concrete core without investigating the whole response under push-out load. In this research, four models are proposed to predict the interfacial behavior in CFST including the post-peak branch under the push-out loading test based on 157 circular specimens and 105 squared specimens from the literature. Two models (one for circular and one for squared CFST) are developed and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 39 publications
(48 reference statements)
1
5
0
Order By: Relevance
“…The slip between the slab and the beam interface contributed to the energy dissipated by the system, and the ductility demands decreased on other parts, such as the beam ends and the joints. Numerical results confirmed the experimental conclusions and revealed that using intermediate and low shear connection degrees with partial-strength joints results in a practical seismic design [11][12][13].…”
Section: Introductionsupporting
confidence: 71%
“…The slip between the slab and the beam interface contributed to the energy dissipated by the system, and the ductility demands decreased on other parts, such as the beam ends and the joints. Numerical results confirmed the experimental conclusions and revealed that using intermediate and low shear connection degrees with partial-strength joints results in a practical seismic design [11][12][13].…”
Section: Introductionsupporting
confidence: 71%
“…The forecast made by the ANN model will be limited to the actual maximal and minimal values. The data are normalised and denormalised using equations ( 1) and (2), respectively [24]:…”
Section: Muslum [11]mentioning
confidence: 99%
“…Additionally, the connection weight-based importance factor approach, proposed by Olden and Jackson, is used to judge the importance of RN and UPV in the 2-5-1 ANN model. This method calculates the total connection weights of every input as the product of input-hidden and hidden-output connection link weights, existing between every input and output, and then adds the products for all hidden nodes to obtain the importance factor [24]. Table 8 lists the importance factor values of RN and UPV based on the connection links weights listed in Table 4.…”
Section: Civil and Environmental Engineeringmentioning
confidence: 99%
“…It has been observed through the literature that there are many existing finite element analyses to predict the bending behaviour of steel tubes [ 36 , 37 , 38 , 39 ]. However, there are no available finite element analyses to evaluate and predict the bending behaviour of circular hollow steel tube sections with openings and presence of rings in the length of the tube, which are necessary to investigate steel tube sections under different loadings and can be used to be a reference for future studies and provide input data for the steel tubes in the finite element (FE) models.…”
Section: Introductionmentioning
confidence: 99%